Positive and negative perfectionism and the big five personality factors - Egan, Sarah; Piek, Jan; Dyck, M. (Cambridge University Press, 2015)
© The Author(s) 2015. Perfectionism has been argued to have both positive and negative aspects. Negative perfectionism has a robust positive correlation with psychopathology. This study explored the personality pattern of a group of clinical participants and a group of athletes in relation to positive and negative perfectionism. The results indicated negative perfectionism is related to neuroticism and agreeableness in both clinical and non-clinical groups. Negative perfectionism was most strongly associated with low agreeableness but had no significant relationship with conscientiousness or extraversion in the clinical sample. In the athlete sample, higher negative perfectionism was most strongly related to higher neuroticism but was also associated with lower extraversion and conscientiousness. In order to more fully understand these relationships and their clinical implications, more studies using validated measures of positive and negative perfectionism with larger samples are required. It would be useful to determine if personality factors of agreeableness and competence could be increased in order to ameliorate the distress associated with negative perfectionism.